2008
DOI: 10.1007/s00705-008-0135-5
|View full text |Cite
|
Sign up to set email alerts
|

Porcine reproductive and respiratory syndrome virus modulates apoptosis during replication in alveolar macrophages

Abstract: Different viruses have evolved strategies that inhibit apoptosis of the host cell early in infection and/or induce apoptosis in the host cell late in infection. In this study, it was investigated if and when porcine reproductive and respiratory syndrome virus (PRRSV) modulates apoptosis in PRRSV-infected macrophages. The PRRSV replication cycle in macrophages was completed within 12 h post-inoculation (hpi). PRRSV-infected macrophages, treated with staurosporine at 4, 5, 6 and 8 hpi, were significantly protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 60 publications
4
89
0
3
Order By: Relevance
“…We have shown that infection of our PBMMWs results in a productive infection similar to that observed in alveolar macrophages and bone marrow-derived dendritic cells (Costers et al, 2008;Lee et al, 2010). Since we observed an earlier peak of virus production (24 h versus 36-48 h), we chose a 24 h time point to assay phagosomal function.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We have shown that infection of our PBMMWs results in a productive infection similar to that observed in alveolar macrophages and bone marrow-derived dendritic cells (Costers et al, 2008;Lee et al, 2010). Since we observed an earlier peak of virus production (24 h versus 36-48 h), we chose a 24 h time point to assay phagosomal function.…”
Section: Discussionmentioning
confidence: 90%
“…3a). In fact, PRRSV replication of macrophages has been shown to depress apoptosis early in infection (Costers et al, 2008). A mechanistic explanation of how PRRSV infection reduces phagosomal proteolysis and phagosome-derived ROS production remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…El induce apoptosis o necrosis de linfocitos (25), en proceso molecular de replicaci贸n es alta y en tan solo consecuencia predispone a la invasi贸n de agentes 6 a 12 hs post-infecci贸n es posible detectar ant铆geno secundarios por comprometimiento de las barreras v铆rico en el citoplasma de las c茅lulas infectadas (23).…”
Section: S铆ndrome Reproductivo Y Respiratorio Porcino (Prrs)unclassified
“…Diversos estudios experimentales coinciden Varios estudios han revelado el papel con que los picos de replicaci贸n viral se observan relevante de las citocinas como mediadores de entre los 7 y 14 d铆as post-inoculaci贸n (DPI) y enfermedad respiratoria viral en cerdos y aunque el postulan que durante la replicaci贸n, las c茅lulas son PRRSV no se comporta como un "cl谩sico" virus conducidas hacia un estadio de anti-apoptosis, de respiratorio es capaz de inducir la producci贸n de forma que cuando la replicaci贸n ha culminado la citocinas pro-inflamatorias y anti-inflamatorias c茅lula entra en apoptosis (23). De esta manera la principalmente en los macr贸fagos septales liberaci贸n del PRRSV se produce mediante la lisis de pulmonares de los animales infectados que la c茅lula infectada (24).…”
Section: S铆ndrome Reproductivo Y Respiratorio Porcino (Prrs)unclassified
See 1 more Smart Citation